Factors Affecting Sukuk Return and Issuance: Insight from Sukuk Market of Türkiye - Ender Baykut (Kocatepe İslami İlimler Dergisi)
Since the first sukuk issuance in 2001, sukuk transaction volumes have been increasing day by day in major financial markets. Sukuk has become an attractive investment tool, especially for US and EU investors, as well as being preferred by investors who embrace Islamic finance principles and shariah compliance. Parallel to increased attention all over the financial markets, also sukuk plays a critical role in facilitating the deepening capital markets of Türkiye. To this end, this paper aims to identify the effect of inflation, deposit interest rate, dollar currency and sukuk issuance size on sukuk return. Furthermore, as a part of the analyses, the causality relationship is tested between macroeconomic variables and sukuk issuance. The Toda-Yamamoto causality test is utilised to rigorously assess the causal relationships between variables. In contrast, the Autoregressive Distributed Lag (ARDL) is applied to detect both short-term and long-term coefficients among the variables, employing a monthly dataset that encompasses the period from 2013 to 2024. Empirical evidence shows the constructed ARDL model is significant at the 1% significance level. On top of that, a significant positive relationship between sukuk returns and deposit interest rate, inflation, and sukuk issuance size might be stated by assessing the long-term coefficients. Only the USD/TRY exchange rate negatively affects sukuk returns as indicated by long-term coefficients. Moreover, the coefficient of error correction model is negative and significant which is developed to get the short-term coefficients. ECM model reflected that 75% of a shock occurs in the short term and these shocks will disappear in the long term. In addition, a Toda-Yamamoto causality test stated that dollar exchange rate and deposit interest rates are the two factors that have a causal relationship with the size of sukuk issuance. This study elucidates the importance of macroeconomic variables on both sukuk return and sukuk issuance. It highlights the factors that sukuk issuers and investors should consider throughout their decision-making process.